Equity as a fundamental economic category in light of accounting standards = Kapitał własny jako fundamentalna kategoria ekonomiczna w świetle standardów rachunkowości - Nowak, Edward (Zielona Góra: Faculty of Economics and Management Press)
Equity is one of the fundamental economic categories which describe the financial position of an enterprise. Equity is a synthetic and complex value which is formed under the influence of multiple factors. The volume and structure of equity depends not only on the actions taken in various areas of activities pursued by a given enterprise but also on external factors. The information about equity is used by various stakeholders in a given enterprise when making economic decisions. Therefore, the method of determining equity and presenting information about it is subject to Polish and international accounting and financial reporting regulations. The present paper presents the essence of equity as a synthetic measure of enterprise performance in light of accounting standards and laws.
Keywords: kapitał własny; sprawozdawczość finansowa; standardy rachunkowości; ocena sytuacji finansowej; equity; financial reporting; accounting standards; financial position assessment